Prognostic significance of E-cadherin expression in prostatic carcinoma: A protocol for systematic review and meta-analysis. Issue 15 (April 2020) - Zhang, Xiwen; Zhang, Zhenhua; Chen, Shuntai; Jiang, Juling; Qi, Runzhi; Mi, Xue; Zhang, Xing; Xi, Yupeng; Zheng, Honggang; Hua, Baojin
Abstract: Background: Increasing studies were performed to explore the prognostic value of E-cadherin in prostatic carcinoma, however, with inconsistent results. Hence, this systematic review is aimed to evaluate the prognostic role of E-cadherin in patients with prostatic carcinoma (PCa). Methods: A comprehensive literature search in all available databases will be conducted to identify eligible studies. We will employ hazard ratios (HRs) and 95% confidence intervals (95% CIs) to estimate the correlations between E-cadherin expression and overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), progression-free survival (PFS) and clinicopathological features. Meta-analysis will be performed using Review Manager (Revman) 5.3.5 software (Cochrane Community, London, United Kingdom) and STATA 14 software (version 14.0; Stata Corp, College Station, TX). Results: This study will provide a high-quality synthesis of current evidence of the correlations between snail expression and OS, DFS/RFS, PFS and clinicopathological features. Conclusion: The study will provide updated evidence to assess whether the expression of E-cadherin is in association with poor prognosis in patients with PCa. Ethics and dissemination: It is not necessary for ethical approval because individuals cannot be identified. The protocol will be disseminated in a peer-reviewed journal or presented at a relevant conference. Prospero registration number: This systematic review protocol has been registered in the PROSPERO network (No. CRD42019128353).